Women, reform and community in early modern England : Katherine Willoughby, Duchess of Suffolk, and Lincolnshire's godly aristocracy, 1519-1580 /: Katherine Willoughby, Duchess of Suffolk, and Lincolnshire's godly aristocracy, 1519-1580. (2008) - Unknown
No abstract available